Soma-esthétique, art et libération - Richard Shusterman (Appareil)
This essay situates somaesthetics as an extension of my work in pragmatist aesthetics and then explores the political dimensions of somaesthetics and some of its practical applications. Refuting the view that concern for the body is only a private rather than political matter, the essay’s main focus is the politics of liberation and the role aesthetics can play in it. Here the work of Frantz Fanon is discussed. Through a critique of Marcuse’s aesthetic theory, I show how somaesthetics provides a necessary supplement to art’s liberational potential. This is because liberation requires a transformation of sensibility and feelings that is necessary for the transformation of attitudes, habits, and actions that is needed for liberational political change. Work on one’s soma – our core tool and locus of sensory perception and affect – provides a more direct, and therefore more effective, way of transforming sensibility than does the viewing of art. Here I compare somaesthetics to the young Marx’s theory of the senses. The essay concludes with a brief discussion of two forms of practical somaesthetics that I practice. First are the practical workshops for designers; and second is my work in performance art with l’Homme en Or, a project of collaboration with the Parisian artist Yann Toma. The essay concludes with a discussion of the philosophical and political import of this distinctively embodied performance art, an example of somaesthetics in action.